Bridging the Gap: Teacher Efficacy and Diagnostic Assessment in Remote Indonesian Schools - Ramly, Ramly; Azis, Azis; Fajar B, Muhammad; Abduh, Amirullah; Asnur, Muhammad Nur Ashar (Universitas Negeri Makassar, 2025)
Research on Diagnostic Assessment (DA) in remote schools in Indonesia is essential, as education in these areas has been a focus of the government attention for several decades and continues for future. This study provides an overview of teachers' readiness in implementing DA, particularly regarding their efficacy and self-perceptions. This study aims to describe teachers' confidence in conducting DA and their perceptions of its benefits for learning. Data were collected from 35 teachers with varying employment statuses and teaching experience using a questionnaire with linear-scale responses. The questionnaire measured efficacy across four aspects using twelve statements and perceptions across three aspects using nine statements. The questionnaire was distributed online via Google Forms. The data were analyzed using descriptive statistics and presented in frequency tables. The findings reveal that teachers in remote schools have a high level of confidence in their ability to implement DA, adapted to the conditions of underdeveloped areas. Teachers perceive DA as fundamentally effective in transforming learning conditions, although it has not yet provided optimal benefits in various related aspects. Its implementation is also considered to be insufficiently intensive. It is concluded that teachers in remote schools are capable of implementing DA and are concerned about the current suboptimal execution of DA. The findings of this study suggest that while teachers in remote areas are confident in their ability to implement DA, further support and resources are necessary to optimize its use. Enhancing training programs and increasing the intensity of DA application could contribute to more effective teaching and learning outcomes, especially in under-resourced and geographically isolated settings